Contractile properties of developing human fetal cardiac muscle. (7th December 2015) - Racca, Alice W.; Klaiman, Jordan M.; Pioner, J. Manuel; Cheng, Yuanhua; Beck, Anita E.; Moussavi‐Harami, Farid; Bamshad, Michael J.; Regnier, Michael
Abstract : Key points: The contractile properties of human fetal cardiac muscle have not been previously studied. Small‐scale approaches such as isolated myofibril and isolated contractile protein biomechanical assays allow study of activation and relaxation kinetics of human fetal cardiac muscle under well‐controlled conditions. We have examined the contractile properties of human fetal cardiac myofibrils and myosin across gestational age 59–134 days. Human fetal cardiac myofibrils have low force and slow kinetics of activation and relaxation that increase during the time period studied, and kinetic changes may result from structural maturation and changes in protein isoform expression. Understanding the time course of human fetal cardiac muscle structure and contractile maturation can provide a framework to study development of contractile dysfunction with disease and evaluate the maturation state of cultured stem cell‐derived cardiomyocytes. Abstract: Little is known about the contractile properties of human fetal cardiac muscle during development. Understanding these contractile properties, and how they change throughout development, can provide valuable insight into human heart development, and provide a framework to study the early stages of cardiac diseases that develop in utero . We characterized the contractile properties of isolated human fetal cardiac myofibrils across 8–19 weeks of gestation. Mechanical measurements revealed that in early stages of gestation there is low specific force and slow rates of force development and relaxation, with increases in force and the rates of activation and relaxation as gestation progresses. The duration and slope of the initial, slow phase of relaxation, related to myosin detachment and thin filament deactivation rates, decreased with gestation age. F‐actin sliding on human fetal cardiac myosin‐coated surfaces slowed significantly from 108 to 130 days of gestation. Electron micrographs showed human fetal muscle myofibrils elongate and widen with age, but features such as the M‐line and Z‐band are apparent even as early as day 52. Protein isoform analysis revealed that β‐myosin is predominantly expressed even at the earliest time point studied, but there is a progressive increase in expression of cardiac troponin I (TnI), with a concurrent decrease in slow skeletal TnI. Together, our results suggest that cardiac myofibril force production and kinetics of activation and relaxation change significantly with gestation age and are influenced by the structural maturation of the sarcomere and changes in contractile filament protein isoforms. Key points: The contractile properties of human fetal cardiac muscle have not been previously studied. Small‐scale approaches such as isolated myofibril and isolated contractile protein biomechanical assays allow study of activation and relaxation kinetics of human fetal cardiac muscle under well‐controlled conditions. We have examined the contractile properties of human fetal cardiac myofibrils and myosin across gestational age 59–134 days. Human fetal cardiac myofibrils have low force and slow kinetics of activation and relaxation that increase during the time period studied, and kinetic changes may result from structural maturation and changes in protein isoform expression. Understanding the time course of human fetal cardiac muscle structure and contractile maturation can provide a framework to study development of contractile dysfunction with disease and evaluate the maturation state of cultured stem cell‐derived cardiomyocytes.